Industrial scale microwave applicator for high temperature alkaline hydrolysis of PET. Issue 5 (22nd May 2018) - Ramopoulos, Vasileios; Link, Guido; Soldatov, Sergey; Jelonnek, John
Abstract: A microwave design for an industrial scale applicator of a continuous microwave assisted depolymerization of polyethylene terephthalate (PET) has been developed. The cavity is designed for use in combination with an Archimedean screw pump to transport the reaction material, surrounded by a cylindrical pipe with a diameter of 250 mm and a length of 250 mm at the 2.45 GHz ISM band. The proposed design is modular and can be easily expanded for the heating of longer reactor tubes. Simulation results show that a homogeneous heating of the process material along the screw axis can be achieved by using a novel cavity design which is based on the TE 1, 0, x – rectangular waveguide cavity mode. The achieved design provides high energy efficiency with a reflected power of less than 10%. It is robust against changes in the permittivity of the reactants. The electromagnetic design is based on the dielectric properties of the solvolytic reaction mixture measured in the relevant temperature range. It is verified over the full range of the expected permittivities.